Mission analysis for Earth to Mars-Phobos distant Retrograde Orbits. (October 2018) - Conte, Davide; Spencer, David B.
Abstract: This paper focuses on the trajectory design for missions destined to explore Mars and/or Phobos departing from Low Earth Orbit (LEO) and arriving into a Mars-Phobos Distant Retrograde Orbit (DRO). Lunar DROs are also briefly explored as an alternative departure location. A Mars-Phobos DRO is a relatively stable environment which would make both the surfaces of Mars and Phobos available for a reasonable propellant expenditure. This paper presents the methodology used to compute LEO to Mars-Phobos DRO trajectories and results regarding required C 3 at launch, v ∞ at arrival, Time-of-Flight ( T O F ), and total Δ V for various Mars-Phobos DROs using full ephemeris planetary data. The results show that propellant-optimal trajectories from LEO to a specified Mars-Phobos DRO could be used as a staging location between Mars and Phobos. Assuming that refueling is available at the targeted DRO, LEO to Low Mars Orbits (LMO) trajectories would have higher total Δ V due to the additional stop at the Mars-Phobos DRO. However, the aformentioned trajectories would have lower Initial Mass in LEO (IMLEO) and thus a lower gear ratio thanks to the added "pit stop" located at the given DRO. This results in a lower overall spacecraft dry mass that needs to be launched into space from Earth's surface. Highlights: Mars-Phobos DROs are explored as arrival destinations in cis-martian space. Trajectory design for Earth to Mars-Phobos DROs are presented. The design methodology is detailed in the paper and numerical examples are provided. Lunar DROs are also explored as possible departure locations. Propellant-optimal solutions for lunar DROs to Mars-Phobos DROs transfers are given.